Residential Mobility and Trust: The Moderating Role of Cognitive Need for Closure. (January 2021) - Zhao, Na; Xu, Kaiqiang; Sun, Ling
This study examined the link between residential mobility and interpersonal trust building. Study 1 revealed a negative association between residential mobility and trust by measuring personal residential-mobility history. Study 2 demonstrated that participants who were momentarily primed with mobility showed a lower investment than participants in the control group in a trust game. The results of Study 3 showed that need for closure moderated the link between residential mobility and trust-building intention. Specifically, lower need-for-closure people had a significantly lower trust tendency in the mobility group than in the stable group. These findings illuminate the underlying influence of need for closure in the link between residential mobility and trust.